Peran Strategis Ulama dalam Pengembangan Ekonomi Syariah - Nasution, Muhammad Yasir (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
The Islamic scholars and its institutions have an important role in strengthening the knowledge and horizons in Muamalat Fiqh and Syariâah economics so such an important role can be effectively implemented. However, in this case the most important things is a commitment; firstly need to be built a strong commitment among the Islamic scholars and the religious teaching institutions to develop syariâah economics, for the welfare of the people and the nation.